2009
DOI: 10.1002/j.1556-6978.2009.tb00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Privileged Identity Exploration: Examining Counselor Trainees' Reactions to Difficult Dialogues

Abstract: In this qualitative study, the authors examined master's‐level counselor trainees' reactions to difficult dialogues in the classroom regarding racism, heterosexism/homophobia, and ableism over a 3‐year period. Using the Consensual Qualitative Research method as introduced by C. E. Hill, B. J. Thompson, and E. N. Williams (1997), the data analysis team analyzed narrative and reaction papers submitted during a didactic course on multiculturalism. Behavioral reactions were identified that form the basis for this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…It was not that these high‐excitement trainees did not experience guilt; instead, it seems that their experience of guilt was shaped by their comingled feelings of excitement. Student emotions seemed to have a more complex and varied presence in the multicultural counseling class than previous researchers (e.g., Paone et al, 2015; Parker et al, 2004; Watt et al, 2009) have suggested. The interaction between negative and positive emotions is such that we may not be able to understand or predict the impact of any one emotion (e.g., guilt) without also understanding the presence of other central emotions (e.g., excitement).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…It was not that these high‐excitement trainees did not experience guilt; instead, it seems that their experience of guilt was shaped by their comingled feelings of excitement. Student emotions seemed to have a more complex and varied presence in the multicultural counseling class than previous researchers (e.g., Paone et al, 2015; Parker et al, 2004; Watt et al, 2009) have suggested. The interaction between negative and positive emotions is such that we may not be able to understand or predict the impact of any one emotion (e.g., guilt) without also understanding the presence of other central emotions (e.g., excitement).…”
Section: Discussionmentioning
confidence: 60%
“…Such opportunities for reflection can include full classroom discussion, partnered conversations, and small groups facilitated by advanced students. In addition, journals or reaction papers (Hipolito‐Delgado et al, 2011; Watt et al, 2009) encourage deeper personal understanding while also allowing for confidential instructor comments. Perhaps early on, these more individual and private activities are preferable for students prone to reactance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Journaling, a personal form of expressive writing, deepens self-reflection, introspection, and provides "clarity regarding issues, concerns, conflicts, and confusions" (Lent, 2009, p. 69). Journal writing invites self-reflection, opening the door to greater self-awareness, and thus promotes professional and personal growth (Gladding, 1987;Griffith & Frieden, 2000;La Torre, 2005;Milling, 2007;Mio & Barker-Hackett, 2003;Pittman, 2005;Watt et al, 2009). Although often presented as a useful intervention for clients and students, counselors can use writing as a method for emotional regulation and self-care.…”
Section: Writing For Wellnessmentioning
confidence: 98%